Dermatofibrosarcoma protuberans of breast - A case report - Kaur, Manmeet; Tiwana, Kanwardeep Kaur; Nibhoria, Sarita; Singla, Nisha (Indian Journal of Case Reports, 2018)
Dermatofibrosarcoma protuberans (DFSP) is best regarded as well differentiated, primary fibrosarcoma of skin. It is an uncommon, slow growing, locally aggressive, and reoccurring but rarely metastasizing tumor of the deep dermis and subcutaneous tissue. Clinically they present as firm solid nodules that arise most frequently on trunk and extremities. DFSP of the breast has been rarely reported. Here, we report a rare case of DFSP of the breast in 47-year-old woman.